Pengaruh ZIS (Zakat Infak dan Shadaqah) Produktif Terhadap Peningkatan Pendapatan Para Mustahik (Studi Kasus di BMT Mekar Da’wah dan Baznas Jakarta Tahun 2005) - Husnul Khatimah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2005)
Management and distribution of zakah, infaq and shadaqah (ZIS) are the fundamental problem in the Islamic economics. At the first time, zakah just collected and distributed with the target to fulfill primary need of mustahik only. Currently the innovative management of zakah through productive financing to mustahik are -the specific phenomena in Islamic economics. This research tend to find the impact of zakah in order to increase income of mustahik that the object of zakah distribution through productive financing and to deeply understanding about how to couching and counseling program by BMT Mekar Da’wah. The results of wilcoxon signed rank shown that the most of